THE INFLUENCE OF A SOLVENT AND SUGAR ADDITION ON PRESERVATION YOUNG COCONUT MEAT - Yunita Fillia Assah (Balai Riset Dan Standardisasi Industri Manado, 2019)
To maintain the quality of food products, post-harvest handling efforts need to be done by processing, preservation, packaging and storage. This study examines the influence of the percentage of sugar and water solution to the shelf life of oil products in the sugar solution. The study was conducted using factorial experiments prepared in a completely randomized design with 2 replications. Factor A is the use of a water solvent, comprising: A1 = coconut water; A2 = mineral water (AMDK). Factor B is a variation of sugar addition (in percentage) which consist of: B1 = 25%; B2 = 35%; B3 = 45%. Packaging is done on 2 types of packaging, namely jar and Stand Up Pouch. Storage is done at room temperature (for a jar packaging) and refrigerators (for Stand Up Pouch packaging). The observation showed that the organoleptic most preferred solvent treatment of coconut water and sugar content of 25%, with the average score is 4 (love) for the assessment of the texture, color, appearance and feel. Meanwhile, in products using jar packaging, coconut products in sugar solution did not last more than 2 days. This can be seen from the number of TPC that is not eligible. Storage in Stand Up Pouch packaging tends to maintain protein and sugar content, while the total number of bacteria and mold / yeast still increase from observation of 2nd and 4th week. Total bacteria in the second week still meet the requirements based on Microbiology Criteria in Foodstuffs according to Perka BPOM RI. 16 year 2016 for the type of processed food of candied fruit, with the amount of 1.88 x 103 for coconut water solvent treatment and 6.77 x 103 for the treatment of common water solvent type.Keyword : Coconut, Sugar solution, preservation